(untitled) (National Administration Journal, 2021)
This article presents the elaboration and the results of the “Inclusive Development Index for Solidary Cooperatives” (IDICS in Portuguese). The Index measures the inclusion of young people and women in 30 cooperatives of family farming in Minas Gerais, Brazil. Its elaboration took place through a participatory process with the cooperatives’ members and managers. IDICS consists of 2 sub-indexes of 18 variables each: The Women’s Inclusion Index (IIM) and the Youth Inclusion Index (IIJ). The collection of data was done through structured questionnaires, applied remotely to the cooperatives. The results suggest a strong heterogeneity among the cooperatives, and the results are related to the size, time of operation of the cooperative and the region of location. Most cooperatives lack progress with regard to their inclusion processes. Therefore, the Index can be a useful tool for planning and identifying good practices.